Management style in internal audit: influence between personal factors and role conflict - Angélica Ferrari; Paulo Roberto da Cunha; Marines Lucia Boff (Revista Contabilidade & Finanças, 2023)
ABSTRACT This article analyzes the leader's management style effect on the relationship between personal factors and role conflict in the internal audit function. It sheds light on the factors per se regarding the presence of role conflict in internal audit, addressing the effects that various management styles of the audit leader can cause in the relationship previously addressed in the literature between personal characteristics and role conflict. Evidence shows that the skills and expertise of leading internal audit executives impact the role played by internal auditors, becoming major insights to be analyzed and understood when delimiting the internal audit function. This article contributes to grasping the impact that aspects at a personal, professional, and interaction level in the management hierarchy in companies can have on the internal audit function. A survey was used involving 218 internal auditors certified by the Institute of Internal Auditors of Brazil (Instituto dos Auditores Internos do Brasil [IIA Brasil]), working in the internal audit area and with active profiles on the professional networking platform LinkedIn. Use of multiple linear regression for data analysis. Personal factors encompass the independence and expertise of internal auditors. Role conflict comprises three dimensions: demand from the organization vs. the auditor profession; auditing vs. consulting; and personal values vs. professional expectations. Management style measures the behavior of immediate superiors in the dimensions of task, relationship, and situational context. As results and contributions, it was evidenced that internal auditor’s commitment to independence and expertise have a negative influence on role conflict. A management style with behaviors aimed at relationships between individuals, carrying out tasks, or adapting to situations, on the part of immediate superiors, contributes to reducing the level of role conflict in the internal audit function.